Assessment of student engagement in Open and Distance Learning for Construction Management / Sheikh Ali Azzran Sh Said ...[et al.] - Sh Said, Sheikh Ali Azzran; Abd Wahab, Siti Rashidah Hanum; Yunos, Julitta; Abidin, Zaihafiz Zainal (UiTM Press, 2021)
The traditional method of teaching and learning have significantly changed in the higher education due to the COVID-19 pandemic. The development of Open and Distance Learning (ODL) offers opportunites for students' to improve their technological literacy especially in managing their academic work and performance from a distance geographical location. Many researchers have made an attempt to investigate the student engagement in relation to various context of higher education. This study assess student engagement towards ODL in construction management studies . A literature review has been conducted to facilitate the aim of this article.The key discussion suggests that ODL has moderate to high level of student engagement. Therefore, this study recommends the adoption of Online Student Engagement (OSE) approach as an instrument in assessing the student engagement through